Pengaruh Lokasi Dan Promosi Terhadap Minat Menjadi Nasabah Bank Syariah Pada Masyarakat Kelurahan Kenali Besar Kecamatan Alam Barajo - Rian Irawan; Ahsan Putra Hafiz; Nurlia Fusfita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out and analyze the influence of location and promotion on interest in becoming a sharia bank customer in the people of the Kenali Besar sub-district, Alam Barajo sub-district. The methods used in this research are quantitative methods and data analysis methods. This sampling method uses the Isaac & Michael formula to obtain a sample of 260 respondents from the people of the Recognize Subdistrict community by distributing a Likert scale questionnaire. The research results show that the location variable has a positive and significant influence on interest in becoming a sharia bank customer. Based on the t test, it is known that the calculated t value is 8.364, while the t table value is 1.969, indicating that 8.364 > 1.969, and the significance level is 0.001 < 0.05, which means that Ha1 is accepted and Ho1 is rejected. Promotion does not have a positive and significant influence on interest in becoming a sharia bank customer. This can be seen based on the results of the t test that the calculated t value is 0.801, while the t table value is 1.969, indicating that 0.801 < 1.969 with a significance value of 0.424 > 0.05, which means that Ha2 is rejected and Ho2 is accepted. Location (X1) and promotion (X2) together have a significant effect on interest in becoming a sharia bank customer (Y). This can be seen from the significance value for location and promotion which is 0.001 < 0.05 and the calculated f value > f table ( 35,406 >3.87). So it can be concluded that Ha is accepted and Ho is rejected. And in the results of the Adjusted R Square (coefficient of determination) the value is 0.692 or 69.2%. This shows that the influence of the independent variables (X1) and (X2) on (Y) has an influence of 69.2% and the remaining 30.8% is influenced by other variables outside this research.